Die verpleegkundige as preseptor in personeelontwikkeling in opleidingshospitale in Namibië - K. Jooste; C. M. Nel (AOSIS, 1993)
A study undertaken in 1991 focused on the role fulfilment of the preceptor in staff development in training hospitals in Namibia. As in the case in many countries the nursing service climate in Namibia is characterised by constant change in the practice of professional nurses. The preceptor must accompany the professional nurses in their personal and professioanl development